2021
DOI: 10.1038/s41372-021-01198-0
|View full text |Cite
|
Sign up to set email alerts
|

Improving the identification of acute kidney injury in the neonatal ICU: three centers’ experiences

Abstract: Objective: To describe 3 different standardized approaches to improving neonatal acute kidney injury (AKI) identification and the impact on AKI identification, incidence, and nephrology consultation and referral.Study Design: Retrospective cohort study in three academic NICUs. We compared AKI identification, AKI incidence, nephrology consultation and nephrology follow-up before and after implantation of local protocols to standardized neonatal AKI identification.Result: Neonatal AKI identification improved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…14,16,17 A recent multicentre study has similarly demonstrated that sCr protocol screening strategies can improve identification of AKI events in the NICU. 10 The rate of AKI in this study falls within the AKI incidence range reported in other studies, though it was lower than the overall rate of AKI in the AWAKEN study. 1,4,14 AKI detection rates may have been higher had we continued to analyse sCr data after 36 weeks PMA.…”
Section: Ta B L E 3 Comparison Of Clinical Features Between Pre-proto...supporting
confidence: 69%
See 2 more Smart Citations
“…14,16,17 A recent multicentre study has similarly demonstrated that sCr protocol screening strategies can improve identification of AKI events in the NICU. 10 The rate of AKI in this study falls within the AKI incidence range reported in other studies, though it was lower than the overall rate of AKI in the AWAKEN study. 1,4,14 AKI detection rates may have been higher had we continued to analyse sCr data after 36 weeks PMA.…”
Section: Ta B L E 3 Comparison Of Clinical Features Between Pre-proto...supporting
confidence: 69%
“…Another multicentre study evaluated different approaches to AKI screening protocols across three academic NICUs and found that each approach was associated with a significant improvement in AKI identification and increased nephrology consultation. 10 After implementation of protocols for identification and management of AKI, clinician diagnosis and recognition of AKI increased from 26% (49/187) to 85% (103/121). 10 Overall, this study suggests there may be multiple successful screening strategies for improving AKI diagnosis and identification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the prevalence of perioperative AKI is higher compared to the general prevalence of AKI in the PHIS database during the same study period. We previously found that neonatal AKI occurs in 1-3% of neonates admitted to a participating NICU when ICD codes are used to identify AKI in PHIS and those rates are lower than what was previously reported in the literature using serum creatinine AKI criteria [18][19][20].…”
Section: Discussionmentioning
confidence: 70%
“…We previously found that neonatal AKI occurs in 1 to 3% of neonates admitted to a participating neonatal intensive care unit (NICU) when ICD codes are used to identify AKI in PHIS and those rates are lower than what was previously reported in the literature using serum creatinine AKI criteria. [18][19][20] Risk factors of AKI in critically ill neonates have been described in multicenter studies, 8 however, the risks and comorbidities associated with perioperative neonatal AKI are less defined and mostly reliant on single-center reports.…”
Section: Discussionmentioning
confidence: 99%